Ta’arudh Al-Adillah : Problem Solving Methods Of Islamic Law - Balya Ziaulhaq Achmadin; M. Imamul Muttaqin (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2022)
The rapid development of the science of fiqh certainly has a correlation with the understanding of the propositions sourced in the Qur'an and Hadith. For instance, there is a legal proposition that when faced with certain problems will find a solution, but not a few laws that come from the Qur'an in the same context cause different arguments in understanding them. The contradiction here is ta'arudh arguments that contradict each other. So in the process of this research using a qualitative approach by prioritizing normative juridical aspects, there is no perspective misalignment. This paper examines the process of solving the problems of Islamic law specifically, considering the development of Islamic law is always dynamic by the conditions of the times. In addition, in understanding the law, of course, it must be correct and by the legal provisions of the arguments, as well as other arguments that have intersecting pros and cons, then in the process of settling Islamic law in this paper, it focuses on solving the problems of Islamic law.